(untitled) (Italian Review of Legal History, 2024)
In legal history, escaping unjust imprisonment and torture has rarely been regarded as a clever way to save one’s life. Despite Matthew 10.23, Christians were not allowed to flee if their faith seemed weak because of it. In the Ius Commune, the escape was seen as an indication that almost seemed like an admission of guilt. Spanish lawyers tried to determine the monarch’s right over life and limb of the imprisoned person. Only later did teachings based on natural law emerge allowing to save oneself. This idea, however, has not yet been generally admitted